Si@SiOx/Graphene Nanosheets Composite: Ball Milling Synthesis and Enhanced Lithium Storage Performance - Tie, Xiaoyong; Han, Qianyan; Liang, Chunyan; Li, Bo; Zai, Jiantao; Qian, Xuefeng (Frontiers in Materials, 2018)
Si@SiOx/Graphene nanosheet (GNS) nanocomposites as high performance anode materials for lithium-ion batteries are synthesized by mechanically blending the mixture of expanded graphite with Si nanoparticles, and characterized by X-ray diffraction, Raman spectrum, field emission scanning electron microscopy and transmission electron microscopy. During the ball milling process, the size of Si nanoparticles will decrease, and the layer of expanded graphite can be peeled off to thin multilayers. Electrochemical performances reveal that the obtained Si@SiOx/GNS nanocomposites exhibit improved cycling stability, high reversible lithium storage capacity and superior rate capability, e.g. the discharge capacity is kept as high as 1055 mAh g-1 within 50 cycles at a current density of 200 mA g-1, retaining 63.6% of the initial value. The high performance of the obtained nanocomposites can be ascribed to GNS prepared through heat-treat and ball-milling methods, the decrease in the size of Si nanoparticles and SiOx layer on Si surface, which enhance the interactions between Si and GNS.